A Meta-Analysis of Social Skills Training and Related Interventions for Psychosis. (11th November 2017) - Turner, David T; McGlanaghy, Edel; Cuijpers, Pim; van der Gaag, Mark; Karyotaki, Eirini; MacBeth, Angus
Abstract: Objective: Evidence suggests that social skills training (SST) is an efficacious intervention for negative symptoms in psychosis, whereas evidence of efficacy in other psychosis symptom domains is limited. The current article reports a comprehensive meta-analytic review of the evidence for SST across relevant outcome measures, control comparisons, and follow-up assessments. The secondary aim of this study was to identify and investigate the efficacy of SST subtypes. Methods: A systematic literature search identified 27 randomized controlled trials including N = 1437 participants. Trials assessing SST against active controls, treatment-as-usual (TAU), and waiting list control were included. Risk of bias was assessed using the Cochrane risk of bias assessment tool. A series of 70 meta-analytic comparisons provided effect sizes in Hedges' g . Heterogeneity and publication bias were assessed. Results: SST demonstrated superiority over TAU ( g = 0.3), active controls ( g = 0.2–0.3), and comparators pooled ( g = 0.2–0.3) for negative symptoms, and over TAU ( g = 0.4) and comparators pooled ( g = 0.3) for general psychopathology. Superiority was indicated in a proportion of comparisons for all symptoms pooled and social outcome measures. SST subtype comparisons were underpowered, although social-cognitive approaches demonstrated superiority vs comparators pooled. SST treatment effects were maintained at proportion of follow-up comparisons. Conclusions: SST demonstrates a magnitude of effect for negative symptoms similar to those commonly reported for cognitive-behavioral therapy (CBT) for positive symptoms, although unlike CBT, SST is not routinely recommended in treatment guidelines for psychological intervention. SST may have potential for wider implementation. Further stringent effectiveness research alongside wider pilot implementation of SST in community mental health teams is warranted.